2017
DOI: 10.1186/s12284-017-0153-6
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of OsHSP18.0-CI Enhances Resistance to Bacterial Leaf Streak in Rice

Abstract: BackgroundThe small heat shock proteins represent a large family of proteins that respond to a wide range of abiotic and biotic stresses. OsHsp18.0-CI confers tolerance to salt and cadmium and interacts with viral RNA-dependent RNA polymerase (RdRp). However, the direct function of OsHsp18.0-CI in resistance against biotic stresses remains unclear in rice.ResultsHere, we report that the expression of OsHsp18.0-CI was up-regulated upon inoculation with RS105, a strain of Xanthomonas oryzae pv. oryzicola (Xoc) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…Compared with traditional NGS technologies, this technology accomplishes single molecule real-time (SMRT) isoform sequencing (Iso-Seq) with long read lengths, uniform coverage, and high accuracy, which renders PacBio RSII very effective at capturing the full catalogue of transcripts and constructs of a comprehensive transcriptome for species without genome sequence [25]. Furthermore, RNA-Seq based on the BGISEQ-500 platform has been applied to gene expression comparisons of different species, developmental stages, and stresses [26, 27]. Currently, to our knowledge, genome-wide transcriptomic analysis of the salinity-responsive genes has not been reported in alfalfa root tips, where is the primary site for the perception of hyperosmotic pressure and ion toxicity [28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional NGS technologies, this technology accomplishes single molecule real-time (SMRT) isoform sequencing (Iso-Seq) with long read lengths, uniform coverage, and high accuracy, which renders PacBio RSII very effective at capturing the full catalogue of transcripts and constructs of a comprehensive transcriptome for species without genome sequence [25]. Furthermore, RNA-Seq based on the BGISEQ-500 platform has been applied to gene expression comparisons of different species, developmental stages, and stresses [26, 27]. Currently, to our knowledge, genome-wide transcriptomic analysis of the salinity-responsive genes has not been reported in alfalfa root tips, where is the primary site for the perception of hyperosmotic pressure and ion toxicity [28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that in maize and other plants, different HSPs express abundantly during pollen development ( Magnard et al , 1996 ; Young et al , 2001 ; Kumar et al , 2015 ). Furthermore, overexpression of sHSPs in plants enhance their tolerance to abiotic stresses ( Ahn and Zimmerman, 2006 ; Maimbo et al , 2007 ; Jiang et al , 2009 ; Chauhan et al , 2012 ), whereas plants with reduced expression of sHSP exhibit compromised tolerance to heat resistance ( Charng et al , 2006 ) and disease ( Maimbo et al , 2007 ; Ju et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, no MR gene against Xoc is identified in rice until now [2], only some cell wall-related genes are associated with rice resistance to Xoc. The overexpression of polygalacturonase-inhibiting protein 1/4 (OsPGIP1/4) and small heat shock protein (OsHsp18.0-Cl) genes enhance resistance to bacterial leaf streak in rice [34][35][36]. The polygalacturonase-inhibiting protein functions in inhibiting the activity of enzymes which secreted by bacteria to degrade cell wall component-pectic polysaccharides [34].…”
Section: Discussionmentioning
confidence: 99%